ANALISIS KESELAMATAN DAN KESEHATAN KERJA PADA DEPARTEMEN PRODUKSI UNIT CANDY DENGAN METODE HAZARD IDENTIFICATION, RISK ASSESSMENT, AND DETERMINING CONTROL DI PT.MYI - Yusuf, Muhammad; Syahabuddin , Agus (Teknologi : Jurnal Ilmiah dan Teknologi, 2025)
MYI is one of the largest food companies in Indonesia. In the production process of this factory, there are various high-risk activities, especially in the Candy production section. The objective of this research is to implement the Hazard Identification, Risk Assessment and Determining Control (HIRADC) method as an effort to prevent work accidents among workers in the Production Department of the Candy Unit at PT. MYI. This research was conducted observationally. Observations were made on the sources of hazards and control efforts. Interviews were conducted with workers in the input, production, and output sections of the Candy Unit at PT. MYI. The research variables include work in the Candy production process, hazard identification, risk assessment, effectiveness of risk control, and residual risk. The results of the hazard identification that has been carried out show that there are 39 potential hazards that can lead to 39 risks. The risk assessment conducted revealed a risk level of Very High for 2 cases, High for 10 cases, Medium for 8 cases, and Low for 19 cases. The recommendations that can be given from this study are that PT. MYI needs to create and socialize work instructions, provide training, create a periodic maintenance checklist, install covers and limit switches, install conveyor covers, regularly check light and noise levels, provide fire extinguishers, and provide a disposal site for hazardous waste (B3).  Keywords: Production hazard risk of the candy unit, HIRARDC, PT. MYI